TEACHING MATERIALS DEVELOPMENT DESCRIPTION ORIENTED OF GUIDED WRITING STRATEGY FOR GRADE IV STUDENTS ELEMENTARY SCHOOL - Afriyal Is; Taufina Taufik; Ramalis Hakim; Darnis Arief; Desyandri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this teaching material development is to produce a teaching material that is a valid, practical, and effective oriented description of Guided Writing. This type of development study with model 4-D models consisting of definition define, design, development, and dissemination (disseminate). Research Data from validity tests is obtained through RPP validation sheets and teaching materials. Practicality Data is collected through an observation sheet of RPP implementation and a response to the teacher and student responses. The effectiveness of students ' learning activities and processes in the form of character assessment and student writing skills. Collected Data is analyzed descriptively. Results of the study of the validity of the instrument teaching materials obtained 98.04 categorized very valid. The results of observations, polls, and interviews with teachers also stated that this teaching material is practical. The results of the effectiveness of teaching materials based on trials and the dissemination of skills assessment of the students ' descriptions for the assessment of the process skills have also been in excellent categories, and the results of the results from the 95.19 trial acquisition in the dissemination process obtained the 95.75 value. The acquisition shows that the teaching materials of a guided strategy-oriented description of the class IV SD that has been produced can be declared valid, practical, and effective.